Tailored approaches grounded on immunogenetic features for refined prognostication in chronic lymphocytic leukemia - Baliakas, Panagiotis; Moysiadis, Theodoros; Hadzidimitriou, Anastasia; Xochelli, Aliki; Jeromin, Sabine; Agathangelidis, Andreas; Mattsson, Mattias; Sutton, Lesley-Ann; Minga, Eva; Scarfò, Lydia; Rossi, Davide; Davis, Zadie; et al. (Haematologica, 2019)
Chronic lymphocytic leukemia (CLL) patients with differential somatic hypermutation status of the immunoglobulin heavy variable genes, namely mutated or unmutated, display fundamental clinico-biological differences. Considering this, we assessed prognosis separately within mutated (M-CLL) and unmutated (U-CLL) CLL in 3015 patients, hypothesizing that the relative significance of relevant indicators may differ between these two categories. Within Binet A M-CLL patients, besides TP53 abnormalities, trisomy 12 and stereotyped subset #2 membership were equivalently associated with the shortest time-to-first-treatment and a treatment probability at five and ten years after diagnosis of 40% and 55%, respectively; the remaining cases exhibited 5-year and 10-year treatment probability of 12% and 25%, respectively. Within Binet A U-CLL patients, besides TP53 abnormalities, del(11q) and/or SF3B1 mutations were associated with the shortest time-to-first-treatment (5- and 10-year treatment probability: 78% and 98%, respectively); in the remaining cases, males had a significantly worse prognosis than females. In conclusion, the relative weight of indicators that can accurately risk stratify early-stage CLL patients differs depending on the somatic hypermutation status of the immunoglobulin heavy variable genes of each patient. This finding highlights the fact that compartmentalized approaches based on immunogenetic features are necessary to refine and tailor prognostication in CLL.
Keywords: chronická lymfatická leukemie; chromozomální aberace; Prognosis; Kaplan-Meier Estimate; Male; imunogenetika; Time-to-Treatment; Biomarkers, Tumor; mutace; Neoplasm Staging; lidé; senioři nad 80 let; senioři; prognóza; Aged; Immunogenetics; čas zasáhnout při rozvinutí nemoci; Disease Susceptibility; ženské pohlaví; staging nádorů; nádorové biomarkery; Aged, 80 and over; Chromosome Aberrations; mužské pohlaví; náchylnost k nemoci; Mutation; Leukemia, Lymphocytic, Chronic, B-Cell; Kaplanův-Meierův odhad; Humans; Female